Effect of weekly high-dose vitamin D3 supplementation on serum cholecalciferol concentrations in pregnant women. Issue 158 (April 2016) - Dimitris, Michelle C.; Perumal, Nandita; Craig-Barnes, Hayley A.; Leadley, Michael; Mahmud, Abdullah A.; Baqui, Abdullah H.; Roth, Daniel E.
Highlights: Pregnant Bangladeshi women had low serum cholecalciferol (D3) concentrations. Weekly vitamin D3 (35, 000 IU/week) significantly increased serum D3 concentrations. Serum D3 remained elevated throughout the week between weekly vitamin D doses. Weekly vitamin D3 supplementation may be a suitable alternative to daily regimens. A clinically relevant threshold serum D3 concentration has not yet been defined. Abstract: Vitamin D status is conventionally defined by the serum concentration of 25-hydroxyvitamin D. However, it has been proposed that the serum cholecalciferol concentration (D3) also determines functional vitamin D sufficiency. The objective of this study was to describe the effect of weekly high-dose vitamin D3 supplementation on inter-dose serum D3 in pregnant women. We conducted a sub-study of a completed randomized double-blind placebo-controlled trial of vitamin D3 (35, 000 IU/week) supplementation in late pregnancy (AViDD trial) in Dhaka, Bangladesh. This study included pregnant women enrolled at 26–29 weeks gestation who fully adhered to the prenatal supplement intervention for ≥8 consecutive weeks and for whom serum samples were available for D3 analysis ( n = 65). Serum D3 was uniformly low at enrolment. Mean D3 increased and was maximal at 1 day after vitamin D dose administration (152.09 nmol/L, SD 25.11 nmol/L) and remained significantly higher in VitD vs. Pl at 7 days (29.59 nmol/L vs. 1.92 nmol/L, p = 0.007). Daily average of the group mean D3 during the week following dosing was 66.97 nmol/L in VitD versus 2.13 nmol/L in Pl. In conclusion, serum D3 remained significantly elevated throughout the week following ≥8 consecutive weekly doses of 35, 000 IU D3 in pregnant women. However, the clinically significant minimum threshold of serum D3 remains to be established.